A perspective on the Society of Thoracic Surgeons Composite Score for evaluating esophagectomy for esophageal cancer - Liang, Shuyin; Luketich, James D.; Sarkaria, Inderpal S. (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
The Society of Thoracic Surgeons General Thoracic Surgery Database (STS GTSD) Task Force has proposed a composite performance measure to evaluate quality of care delivered to patients undergoing esophagectomy for esophageal cancer (1). The Task Force summarized clinical data from GTSD version 2.2 between January 01, 2012 to December 31, 2014 for the participating programs, and compared them to the National Inpatient Sample (NIS).